PERAN ORGANISASI PENDIDIKAN DALAM MENINGKATKAN PROFESIONALISME GURU DI SD NEGERI 01 TULUS AYU - Khasbi Ainun Najib; Reva Azzahra; Gita Amalya; Sri Wahyuningsih (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Teacher professionalism is an important aspect in creating a quality learning process, so that educational organizations act as facilitators to support the development of teacher competence. This research aims to explore various programs, strategies and activities implemented by educational organizations to encourage improvements in teachers' pedagogical, social and professional abilities.  This research uses descriptive qualitative methods with interview techniques, observations used by researchers to collect data, and researchers carry out document analysis to strengthen a fact or use it to strengthen an argument. The results of this research will be that the researcher reveals that educational organizations play a strategic role in increasing teacher professionalism at SD Negeri 01 Tulusayu. The recommendations provided include strengthening training programs based on teacher needs, increasing resources, and stronger synergy between educational organizations and schools to support the sustainable development of teacher professionalism.